2019
DOI: 10.1186/s12917-019-2011-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of carriage of CTX-M-15 in faecal Escherichia coli in horses at an equine hospital in the UK; increasing prevalence over a decade (2008–2017)

Abstract: Background This study investigated changes over time in the epidemiology of extended-spectrum β-lactamase (ESBL) producing Escherichia coli within a single equine referral hospital in the UK. Faecal samples were collected from hospitalised horses in 2008 and 2017, processed using selective media and standard susceptibility laboratory methods. A novel real-time PCR with high resolution melt analysis was used to distinguish bla CTX-M-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…The main bacterial species in all cohorts was E. coli, with decreased incidence on admission and during hospitalization, due to increased incidence of other nosocomial ESBL-producing bacterial species. The main ESBL gene group was CTX-M-1, as was previously reported in community horses [26]. However, on admission and during hospitalization, CTX-M-1 incidence decreases, alongside an increase in the number of ESBL genes.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The main bacterial species in all cohorts was E. coli, with decreased incidence on admission and during hospitalization, due to increased incidence of other nosocomial ESBL-producing bacterial species. The main ESBL gene group was CTX-M-1, as was previously reported in community horses [26]. However, on admission and during hospitalization, CTX-M-1 incidence decreases, alongside an increase in the number of ESBL genes.…”
Section: Discussionsupporting
confidence: 69%
“…However, on admission and during hospitalization, CTX-M-1 incidence decreases, alongside an increase in the number of ESBL genes. A study conducted in an equine hospital in the UK demonstrated the emergence of ESBL-producing E. coli during a decade [26], whereas we demonstrated a significant increase in ESBL-E shedding during individual horses' hospitalization. These findings support an urgent necessity in active surveillance and infection control programs in veterinary facilities and hospitals.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Drug resistance genes in general, and especially ESBL genes may originate from the environment, including manure, air and other animals. In recent studies, CTX-M-15 was identified as an emerging enzyme in human and in veterinary medicine in general and specifically in horses [7], but was not identified in this study. Drug resistance genetic variation may be also influenced by different facilities and interfaces [18].…”
Section: Discussionmentioning
confidence: 69%
“…Penicillins and cephalosporins are commonly prescribed in horses [6] and ESBL-E were reported as colonizing and infecting horses. In a longitudinal study in an equine clinic in the UK, increasing carriage rates were reported over a decade [7]. Reported infections in horses include wounds, respiratory, urinary tract and umbilical infections [8][9][10].…”
Section: Introductionmentioning
confidence: 99%